THE IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) IN STUDENTS WRITING SKILLS ON ANALYTICAL EXPOSITION TEXT - Asyiva Kusumahati; BA Prabowo Kusumo Adi; Sumarjo (STKIP Subang, 2023)
Problem based learning is an approach that makes the students think critically to solve problems. Because in writing a text, students have to make a statement that should be critical. Especially when writing an analytical exposition text in which they should persuade the readers to agree with their statements. Therefore, this study aimed to know whether implementing problem-based learning in analytical exposition text affects the students' writing skills. This quantitative study used pre-experimental method where the writers carried out a pretest and posttest for 36 students as participation. This study was conducted in one of the ULP classes in SMK N 2 Semarang in the academic year 2022/2023. The pretest and posttest data were analyzed using a writing assessment rubric. This study found out if the students' score increased where the mean score pretest was 69.33 to 89.41 for the posttest. So, it was shown that PBL significantly affects students’ writing skills in making an analytical exposition test